FAKTOR – FAKTOR YANG MEMPENGARUHI PEMILIHAN MODEL REVALUASI SEBAGAI MODEL PENGUKURAN ASET TETAP DAN DAMPAKNYA TERHADAP MANAJEMEN LABA - Rini Martini; Kurniawati Kurniawati (Universitas Bunda Mulia, 2018)
Since the emergence of the revaluation model as another option in the measurement of fixed assets, the participation of public companies in Indonesia in the implementation of fair value began to increase. The aim of this study is to investigate factors that affecting the decisions made by the company to perform revaluation model of fixed asset and the effect of revaluation model on earnings management. The sample used in this research were non financial companies listed at Indonesia Stock Exchange 2013-2015. Samples are collected by purposive sampling and resulted in 180 firms as the final sample. The statistic method used was binary logistic regression method, with hypotheses testing of statistic t using a significance level (α) = 5%. The statistical tool used is SPSS 23. The result of this research indicates that company value has negative significant influence and fixed asset intensity has positive significant influence on revaluation model implementation. Meanwhile leverage and liquidity do not have significant influence on revaluation model implementation. Revaluation model implementation does not have significant influence on earnings management. This research also showed that asset revaluation implementation can be used to reduce information asymmetry and give positive signal to financial statement users. But apparently asset revaluation implementation does not have significant influence with earnings management because fair value implementation has not been optimal in Indonesia's public company.Keywords : Fixed asset, revaluation model, leverage, liquidity, company value, fixed asset intensity, earnings management.